2018
DOI: 10.1055/s-0038-1636544
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Spine Fractures in Children: Evaluation, Management, and Future Directions

Abstract: Fractures of the tibial spine are estimated to occur in 3 per 100,000 children annually, but account for 2 to 5% of pediatric knee injuries with effusion. Although these fractures were historically associated with bicycle accidents, the surge of organized youth sports in recent decades has brought renewed attention to this injury. While minimally displaced fractures can be treated nonoperatively, several techniques have been described for fixation of displaced or comminuted fractures. Sequelae of this injury c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 103 publications
1
27
0
Order By: Relevance
“…The management of TSA still raises controversies. To date, it is widely accepted that undisplaced fractures (type I) are better managed conservatively, while major displacement (type III and IV) should require surgical repair [ 31 ]. The main concern remains the treatment of mild to moderate displacement in type II TSA fractures…”
Section: Discussionmentioning
confidence: 99%
“…The management of TSA still raises controversies. To date, it is widely accepted that undisplaced fractures (type I) are better managed conservatively, while major displacement (type III and IV) should require surgical repair [ 31 ]. The main concern remains the treatment of mild to moderate displacement in type II TSA fractures…”
Section: Discussionmentioning
confidence: 99%
“…20 Recent literature acknowledges that MRI is an important pretreatment evaluation method for tibial spine fractures; yet, there is a paucity of studies on the effect of pretreatment MRI in identifying concomitant injury and patient outcomes in pediatric patients. 1 The primary aim of this study was to evaluate and compare rates of identified concomitant injury in patients with and those without pretreatment MRI. We hypothesized that patients with pretreatment MRI would have a higher rate of identified concomitant injuries than those without.…”
mentioning
confidence: 99%
“…5,32 The few TSF studies discussing this topic generally noted a higher incidence of arthrofibrosis with high-energy injury mechanisms and concomitant ligamentous or meniscal injuries without reporting it as a specific risk factor. 1 We found that traumatic injuries not resulting from athletics increased the risk of arthrofibrosis development nearly 3-fold in multivariate analysis. Grouping injury activity as sports related or not (trauma related) and creating a traumatic injury activity grouping (motor vehicle crash, bicycle accident, fall from height, or horseplay/fighting) both reached significance in analysis.…”
Section: Discussionmentioning
confidence: 72%